Hot rod empire : Robert E. Petersen and the creation of the world's most popular car and motorcycle magazines /: Robert E. Petersen and the creation of the world's most popular car and motorcycle magazines. (2018) - Stone, Matthew L, 1958-; Carleton, Gigi
No abstract available